Voluntary leadership and asymmetric endowments in the investment game - Fabian Kleine; Manfred Königstein; Balázs Rozsnyói (Games, 2018)
We experimentally investigate variants of the investment game by Berg, Dickhaut, and McCabe (1995), in which one of the two players decides who are first mover and second mover. It has been shown by Kleine, Königstein, and Rozsnyói (2014) that voluntary leadership increases both investment and backtransfer. We interpret voluntary leadership as a signal of cooperation that stimulates reciprocal cooperation. If a relatively rich player takes the lead (putting himself/herself under investment risk) this should be seen as a less strong signal of cooperation than taking the lead among equally endowed players. Indeed, we show that under asymmetric endowments, voluntary leadership has a weaker effect than under symmetric endowments.
Keywords: C70; C90; D90; 330; experiment; cooperation; leadership; endowment asymmetry